Predictocracy : market mechanisms for public and private decision making - Abramowicz, Michael (Yale University Press, 2007)
Predicting the future is serious business for virtually all public and private institutions, for they must often make important decisions based upon such predictions. This text explores how institutions might improve their predictions and arrive at better decisions by means of prediction markets.